2023
DOI: 10.3390/ijms241210255
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Transcriptional Changes in Response to Stress in Patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: A Pilot Project

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex, multi-symptom illness characterized by debilitating fatigue and post-exertional malaise (PEM). Numerous studies have reported sex differences at the epidemiological, cellular, and molecular levels between male and female ME/CFS patients. To gain further insight into these sex-dependent changes, we evaluated differential gene expression by RNA-sequencing (RNA-Seq) in 33 ME/CFS patients (20 female, 13 male) and 34 matched healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(96 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies have identified sex-specific changes in RNA or microRNA profiles from PBMCs in ME/CFS. 28 , 29 We also performed correlation analyses between gene expression profiles of classical monocytes from all of the female samples and identified higher correlations within the same subject (self) over interindividual comparisons. Notably, interindividual variations among cases were higher than controls, consistent with ME/CFS heterogeneity ( Figure S3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified sex-specific changes in RNA or microRNA profiles from PBMCs in ME/CFS. 28 , 29 We also performed correlation analyses between gene expression profiles of classical monocytes from all of the female samples and identified higher correlations within the same subject (self) over interindividual comparisons. Notably, interindividual variations among cases were higher than controls, consistent with ME/CFS heterogeneity ( Figure S3 B).…”
Section: Resultsmentioning
confidence: 99%
“…B., dass sich bei Menschen mit ME/CFS und Immundefekten andere potenzielle Marker nachweisen ließen als bei Betroffenen ohne zusätzlichen Immundefekt [ 51 ]. Bei Patient:innen mit PCS und ME/CFS zeigte sich, dass auch Frauen und Männer unterschiedliche Marker aufweisen [ 52 , 53 ]. Zudem könnte hier auch die Dauer der Erkrankung sowie der aktuelle Gesundheitszustand der Patient:innen (beispielsweise Gesundheitszustand ohne akute Exazerbation durch post-exertionelle Malaise (PEM) und während der PEM (siehe unten)) eine Rolle spielen, wie Xiong et al.…”
Section: Diagnostik Von Me/cfsunclassified
“…Multiple viral infections have long been implicated in the onset and chronicity of ME/CFS pathology, but no single pathogen has been identified. Viruses predominantly linked to ME/CFS belong to the family of herpesviruses that include large double-stranded DNA viruses, notably Epstein-Barr virus (EBV) [51][52][53][54][55][56][57], human herpesvirus-6 (HHV-6) [58][59][60], HHV-7 [58,59], herpes simplex virus-1 (HSV-1), and HSV-2 [3,7,61]. Herpesviruses are common infectious agents within the general population that establish life-long latency in humans.…”
Section: Introductionmentioning
confidence: 99%